Rearrangement of 2-azanorbornenes to tetrahydrocyclopenta[c]pyridines under the action of activated alkynes – A short pathway for construction of the altemicidin core. Issue 46 (15th November 2017) - Nasirova, Dinara K.; Malkova, Anastasia V.; Polyanskii, Kirill B.; Yankina, Kristina Yu.; Amoyaw, Prince N.-A.; Kolesnik, Irina A.; Kletskov, Alexey V.; Godovikov, Ivan A.; Nikitina, Eugeniya V.; Zubkov, Fedor I.
Graphical abstract: Highlights: Amino-Claisen rearrangement of azabicyclo[2.2.1]heptenes under the action of alkynes. Diastereoselective pathway to altemicidin and dinklageine core analogs. Effective synthesis of 2, 4a, 7, 7a-tetrahydrocyclopenta[ c ]pyridines under mild conditions. Short pathway for construction of the altemicidin core. Abstract: A simple approach to a series of 2, 4a, 7, 7a-tetrahydro-1 H -cyclopenta[ c ]pyridines was proposed on the basis of the amino-Claisen rearrangement of readily accessible 2-azabicyclo[2.2.1]hept-5-enes under the action of dialkyl acetylenedicarboxylates, methyl propiolate or propiolamide. The rearrangement is highly diastereoselective and leads to the formation of only one isomer with cis -annulation of the five- and six-membered rings in satisfactory yields. Using the developed method, close analogs of the altemicidin and SB-203207 cores were synthesized.